The existence of tourist visits in samboja, indonesia: a prediction - Maria, Siti; Lestari, Dirga; Darma, Dio Caisar (Journal of Business on Hospitality and Tourism, 2022)
In the last few decades, tourism communities have continued to improve to develop destination attributes. The interest of tourists is certainly a reference that contains hope and reality after they visit a destination. Samboja is one area that has the most tourist destinations, both at the level of Kutai Kartanegara Regency and East Kalimantan Province (Indonesia). However, their natural destinations as beaches are not yet a priority for the local community, so their income from their development is still minimal. Through a semi-structured survey approach to 185 respondents (visitors) in four predetermined destinations, we dig deeper into the extent of the predictions of the existence of tourist visits (ETV) with several influencing variables. Regression estimates prove that tourist income, travel costs, and travel time have had a significant impact on ETV. From a similar test, the cost of travel to other attractions and facilities actually has an insignificant effect on ETV. The empirical evidence from this study is likely to be the right policy and can be applied by the tourism development community there.